L’évolution de la recherche sur les systèmes coralliens (1960-2007) - Virginie Duvat (VertigO)
This paper presents the evolution of scientific research on coral reef systems in the field of environment sciences. Coral reef systems were a favourable scientific subject for the development of pluri and interdisciplinarity research. In the 1970’s, a coral reef science emerged on common conceptual, methodological and thematical basis. The 1990’s opened a new period in the evolution of coral reef research, characterized by the development of transdisciplinarity.